Efficient Isolation of Cardiac Stem Cells from Brown Adipose. (18th April 2010) - Liu, Zhiqiang; Wang, Haibin; Zhang, Ye; Zhou, Jin; Lin, Qiuxia; Wang, Yanmeng; Duan, Cuimi; Wu, Kuiwu; Wang, Changyong
Abstract : Cardiac stem cells represent a logical cell type to exploit in cardiac regeneration. The efficient harvest of cardiac stem cells from a suitable source would turn promising in cardiac stem cell therapy. Brown adipose was recently found to be a new source of cardiac stem cells, instrumental to myocardial regeneration. Unfortunately, an efficient method for the cell isolation is unavailable so far. In our study we have developed a new method for the efficient isolation of cardiac stem cells from brown adipose by combining different enzymes. Results showed that the total cell yield dramatically increased (more than 10 times, P < .01 ) compared with that by previous method. The content of CD133-positive cells (reported to differentiate into cardiomyocytes with a high frequency) was much higher than that in the previous report (22.43% versus 3.5%). Moreover, the isolated cells could be the efficiently differentiated into functional cardiomyocytes in optimized conditions. Thus, the new method we established would be of great use in further exploring cardiac stem cell therapy.